PENGEMBANGAN MEDIA PEMBELAJARAN KETERAMPILAN MENYIMAK DAN MEMBACA BERBASIS MULTIMEDIA INTERAKTIF SISWA KELAS IV SEKOLAH DASAR - Endang Sri Maruti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
This research aims to develop interactive multimedia-based instructional media in order to improve students' listening and reading skills. This research refers to the development of 4-D method. 33 test subjects as children. Validation of research instruments are sheets, observation sheets, questionnaires, and learning tests. Data collection techniques used validation and observation techniques. Techniques of data analysis used qualitative descriptive data. Lesson plan results demonstrate feasibility can be trusted with a good reliability of the instrument category. The observation of student activity meets the criteria specified limits effectiveness. Based on the questionnaire responses of students, learning with interactive CD was interesting. Student learning outcomes showed positive development. Thus, the products developed have been effective.